CHARACTERISTICS OF PEOPLE WHO EXPERIENCED RURAL EXODUS IN A TOWN ON THE WESTERN BORDER OF THE STATE OF RIO GRANDE DO SUL - Kirchner, Rosane Maria; Saidelles, Ana Paula Fleig; Santos, Nara Zamberlan dos; Benetti, Joana Kirchner; Stumm, Eniva Miladi (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The increasing migration of people from countryside to the cities, registered in the past century, caused a series of difficulties to these workers and required their adaptation to urban conditions. The quantitative and descriptive research, case study, carried out in São Gabriel City, western border of the State of Rio Grande do Sul, located in the southern half of the state, was developed amongst citizens who moved from countryside to the urban area. Results showed that the enterviewed people nowadays develop actitivies as autonomous workers and as employees. Results also showed that, although part of the enterviewed people have informal jobs and face difficulties to find schools for their children, most of them own their own houses. The data confirms the difficulties faced by these people, but also demonstrates the efforts to minimize inequalities imposed by society.